No increased risk of transfusion‐transmissible infections after tattooing, body piercing, or acupuncture among blood donors in the Netherlands. Issue 8 (22nd June 2019) - Prinsze, Femmeke J.; van de Laar, Thijs; Slot, Ed; de Jong, Maarten; Bokhorst, Arlinke; de Kort, Wim; Zaaijer, Hans; van den Hurk, Katja
Abstract : BACKGROUND: In the Netherlands, needle‐related events (NREs) including tattoos, piercings, and acupuncture are a reason for temporary blood donor deferral. This study aims to evaluate whether donors with recent NREs had a higher risk of transfusion‐transmissible infections (TTIs) compared to donors without recent NREs. STUDY DESIGN AND METHODS: Data from 2006 through 2015 on all blood donation attempts in the Netherlands were collected. Multivariate regression models (for repeated measurements) were used to assess the associations between recent NREs and the acquisition of TTIs. Posttest counseling data were used to determine the most likely risk factor in TTI‐positive new and repeat donors. RESULTS: Recent NREs were documented in 97, 518 out of 9, 266, 036 (1.1%) donation attempts; 14, 097 (14.5%) NREs resulted in NRE‐based donor deferral. Recent NREs reported pre‐donation were not associated with an increased risk for TTIs. A total of 29 out of 287 TTI‐positive donors (11 repeat donors, 18 new donors) reported a recent NRE pre‐ and/or post‐donation. Recent NREs, all needle‐stick injuries, were the likely route of transmission in 12 out of 287 (4.2%) of TTI‐positive donors. The donor health questionnaire (DHQ) identified only 1 out of 12 TTI‐linked NREs. Non‐return after NRE deferral, any deferral, or no deferral was 24, 15, and 5%, respectively. DISCUSSION: Recent tattoos, body piercings, or acupuncture were not associated with an increased risk for TTIs in Dutch donors. Given the lower return rates of donors following a temporary NRE‐based deferral, we advocate ending blood donor deferral policies for acupuncture, tattooing, and body piercings, but not needle‐stick injuries, in countries where these practices can be considered safe.